Enhancing Digital Banking Experience Through Text Mining of e-Service Reviews in Indonesia - Tomasaputra, Diarista; Siallagan, Manahan (Ekonomis: Journal of Economics and Business, 2025)
This study aims to assess the service quality of digital-only banks in Indonesia through sentiment analysis and topic modeling of Google Play Store reviews, with a focus on SeaBank, Bank Jago, and Bank Neo Commerce three of the country’s leading digital banks by total assets and user base. Using the E-S-QUAL framework, this research identifies five key service quality dimensions: Efficiency, Fulfillment, Reliability, Responsiveness, and Privacy. The study employs a fine-tuned BERT model to classify sentiment and extract themes from 277,877 reviews. The findings reveal that SeaBank leads in overall performance, particularly in efficiency, with 89.4% of positive sentiment, indicating operational excellence and strong emotional engagement with users. However, gaps in customer service responsiveness were also identified. Bank Jago performs well in efficiency but faces critical issues in reliability, especially related to authentication and device restrictions. Bank Neo Commerce demonstrates the most fragmented sentiment pattern, with systemic weaknesses in reliability and responsiveness. The results offer practical insights for digital banks to improve specific service areas and enhance customer satisfaction. This study contributes to digital banking research by demonstrating how advanced text mining can reveal nuanced service quality patterns directly from user feedback.